Analysis of the pathogenicity of novel GNE mutations and clinical, pathological, and genetic characteristics of GNE myopathy in Chinese population - Yingming Xing; Lingqian Zhao; Renlong Zhao; Qiyun Liu; Juan Wang; Le Wang; Wei Zhang; Junhong Guo; Rongjuan Zhao; Xueli Chang (Orphanet Journal of Rare Diseases)
Abstract Background GNE myopathy is a rare autosomal recessive distal myopathy caused by mutations in UDP-N-acetylglucosamine 2-epimerase/N-acetylmannosamine kinase (GNE), a bifunctional enzyme critical for sialic acid biosynthesis. This study aimed to describe a novel autosomal recessive GNE pedigree in a Chinese family and explore the possible mechanism of GNE variants in GNE myopathy, the most common distal myopathy in China. The clinical, genetic, and pathological characteristics of 216 Chinese patients with GNE myopathy were also summarized. Methods The proband and her family underwent a comprehensive medical history assessment and neurological examinations. Whole-exome sequencing was performed on the proband, and Sanger sequencing was performed on family members. 293T cell lines were used for immunofluorescence (IF), Western blot, and dual-luciferase reporter assays. We collected the clinical data of 216 GNE myopathy patients from previous reports up until August 1, 2024. Patients were classified into distinct groups according to mutation location to analyze genotype-phenotype correlation. Results Whole-exome sequencing of the proband and Sanger sequencing of all available family members identified a compound heterozygous mutation involving a novel promoter region mutation, c.-259T > C, and a reported mutation, c.88 C > T (p.Q30*). The GNE promoter fragment (-500 to -1; c.-259T > C) was cloned to construct the firefly luciferase reporter vector. The dual-luciferase reporter assay showed that the mutated promoter exhibited reduced transcriptional activity, resulting in decreased GNE expression. Western blot and IF analysis of overexpressing Q30* revealed that it reduced GNE expression without altering cellular localization and increased the ectopic cytoplasmic expression of TDP-43. The p.D207V mutation was the most common variant in China. Patients carrying p.D207V tended to experience later disease onset. In the epimerase/epimerase group, men experienced earlier disease onset than women (p < 0.05). In other groups, age at disease onset in females was earlier than that in males. Conclusions The c.-259T > C mutation decreases promoter activity, while the c.88 C > T (p.Q30*) mutation reduces GNE expression and affects TDP-43 distribution, thus affecting normal cellular function. The p.D207V mutation is the most common GNE variant in China and is associated with milder disease progression.